Oxygen Uptake Kinetics Is Slower in Swimming Than Arm Cranking and Cycling during Heavy Intensity - Sousa, Ana; Borrani, Fabio; Rodríguez, Ferran A.; Millet, Grégoire P. (Frontiers in Physiology, 2017)
Oxygen uptake (V̇O2) kinetics has been reported to be influenced by the activity mode. However, only few studies have compared V̇O2 kinetics between activities in the same subjects in which they were equally trained. Therefore, this study compared the V̇O2 kinetics response to swimming, arm cranking, and cycling within the same group of subjects within the heavy exercise intensity domain. Ten trained male triathletes (age 23.2 ± 4.5 years; height 180.8 ± 8.3 cm; weight 72.3 ± 6.6 kg) completed an incremental test to exhaustion and a 6-min heavy constant-load test in the three exercise modes in random order. Gas exchange was measured by a breath-by-breath analyzer and the on-transient V̇O2 kinetics was modeled using bi-exponential functions. V̇O2peak was higher in cycling (65.6 ± 4.0 ml·kg-1·min-1) than in arm cranking or swimming (48.7 ± 8.0 and 53.0 ± 6.7 ml·kg-1·min-1; P < 0.01), but the V̇O2 kinetics were slower in swimming (1 = 31.7 ± 6.2 s) than in arm cranking (19.3 ± 4.2 s; P = 0.001) and cycling (12.4 ± 3.7 s; P = 0.001). The amplitude of the primary component was lower in both arm cranking and swimming (21.9 ± 4.7 and 28.4 ± 5.1 ml·kg-1·min-1) compared with cycling (39.4 ± 4.1 ml·kg-1·min-1; P = 0.001). Although the gain of the primary component was higher in arm cranking compared with cycling (15.3 ± 4.2 and 10.7 ± 1.3 ml·min-1·W-1; P = 0.02), the slow component amplitude, in both absolute and relative terms, did not differ between exercise modes. The slower V̇O2 kinetics during heavy-intensity swimming is exercise-mode dependent. Besides differences in muscle mass and greater type II muscle fibres recruitment, the horizontal position adopted and the involvement of trunk and lower-body stabilizing muscles could be additional mechanisms that explain the differences between exercise modalities.